Couple-Based HIV Counseling and Testing: a Risk Reduction Intervention for US Drug-Involved Women and Their Primary Male Partners. - McMahon, James M; Pouget, Enrique R; Tortu, Stephanie; Volpe, Ellen M; Torres, Leilani; Rodriguez, William (Prevention science : the official journal of the Society for Prevention Research, 2014)
To help reduce the elevated risk of acquiring HIV for African-American and Latina women drug users in primary heterosexual relationships, we developed a brief couple-based HIV counseling and testing prevention intervention. The intervention was based on an integrated HIV risk behavior theory that incorporated elements of social exchange theory, the theory of gender and power, the stages-of-change model, and the information-motivation-behavior skills model. In this article, we describe the development, content, and format of the couple-based HIV testing and counseling intervention, and its delivery to 110 couples (220 individuals) in a randomized effectiveness trial, the Harlem River Couples Project, conducted in New York City from 2005 to 2007. Components of the couple-based intervention included a personalized dyadic action plan based on the couple's risk profile and interactive exercises designed to help build interpersonal communication skills, and facilitated discussion of social norms regarding gender roles. The couple-based HIV testing and counseling intervention significantly reduced women's overall HIV risk compared to a standard-of-care individual HIV testing and counseling intervention. Experiences and perceptions of the intervention were positive among both clients and interventionists. The study was the first to demonstrate the effectiveness and feasibility of delivering a brief couple-based HIV counseling and testing intervention to reduce risk among drug-using heterosexual couples in high HIV prevalent urban communities in the USA. The intervention can be expanded to include new HIV prevention strategies, such as pre-exposure prophylaxis. Further research is needed to evaluate cost-effectiveness and implementation of the intervention in clinical settings.